The role of fibroblast – Cardiomyocyte interaction for atrial dysfunction in HFpEF and hypertensive heart disease. (June 2019) - Bode, David; Lindner, Diana; Schwarzl, Michael; Westermann, Dirk; Deissler, Peter; Primessnig, Uwe; Hegemann, Niklas; Blatter, Lothar A.; van Linthout, Sophie; Tschöpe, Carsten; Schoenrath, Felix; Soltani, Sajjad; et al.
Abstract: Aims: Atrial contractile dysfunction is associated with increased mortality in heart failure (HF). We have shown previously that a metabolic syndrome-based model of HFpEF and a model of hypertensive heart disease (HHD) have impaired left atrial (LA) function in vivo (rat). In this study we postulate, that left atrial cardiomyocyte (CM) and cardiac fibroblast (CF) paracrine interaction related to the inositol 1, 4, 5-trisphosphate signalling cascade is pivotal for the manifestation of atrial mechanical dysfunction in HF and that quantitative atrial remodeling is highly disease-dependent. Methods and results: Differential remodeling was observed in HHD and HFpEF as indicated by an increase of atrial size in vivo (HFpEF), unchanged fibrosis (HHD and HFpEF) and a decrease of CM size (HHD). Baseline contractile performance of rat CM in vitro was enhanced in HFpEF. Upon treatment with conditioned medium from their respective stretched CF (CM-SF), CM (at 21 weeks) of WT showed increased Ca 2+ transient (CaT) amplitudes related to the paracrine activity of the inotrope endothelin (ET-1) and inositol 1, 4, 5-trisphosphate induced Ca 2+ release. Concentration of ET-1 was increased in CM-SF and atrial tissue from WT as compared to HHD and HFpEF. In HHD, CM-SF had no relevant effect on CaT kinetics. However, in HFpEF, CM-SF increased diastolic Ca 2+ and slowed Ca 2+ removal, potentially contributing to an in-vivo decompensation. During disease progression (i.e. at 27 weeks), HFpEF displayed dysfunctional excitation-contraction-coupling (ECC) due to lower sarcoplasmic-reticulum Ca 2+ content unrelated to CF-CM interaction or ET-1, but associated with enhanced nuclear [Ca 2+ ]. In human patients, tissue ET-1 was not related to the presence of arterial hypertension or obesity. Conclusions: Atrial remodeling is a complex entity that is highly disease and stage dependent. The activity of fibrosis related to paracrine interaction (e.g. ET-1) might contribute to in vitro and in vivo atrial dysfunction. However, during later stages of disease, ECC is impaired unrelated to CF.